2012
DOI: 10.1074/jbc.m111.289728
|View full text |Cite
|
Sign up to set email alerts
|

IRF-4 Suppresses BCR/ABL Transformation of Myeloid Cells in a DNA Binding-independent Manner

Abstract: Background: IRF-4 functions both as an oncoprotein and as a tumor suppressor in different cell context. Results: We found that IRF-4 inhibits BCR/ABL transformation of myeloid cells independent of its DNA binding and nuclear localization. Conclusion:The oncogenic and tumor suppressor functions of IRF-4 involve distinct pathways. Significance: The studies help to develop improved therapies for malignancies involving IRF-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These findings indicate that high levels of IRF4 inhibit the survival of CLL cells through means that are independent of its role as a transcriptional regulator. It is worth noting that our finding is in line with a recent study that shows that IRF4, without its DNA binding domain, can still suppress BCR/ABL (Abelson tyrosine kinase) oncogene-induced myeloid leukemia (49). Their analysis further shows that it is the C-terminal IRF ϩ/Ϫ CLL clones as well as three independent NZB IRF4 ϩ/ϩ B1 cells were used for Western blot analysis.…”
Section: Irf4supporting
confidence: 88%
See 1 more Smart Citation
“…These findings indicate that high levels of IRF4 inhibit the survival of CLL cells through means that are independent of its role as a transcriptional regulator. It is worth noting that our finding is in line with a recent study that shows that IRF4, without its DNA binding domain, can still suppress BCR/ABL (Abelson tyrosine kinase) oncogene-induced myeloid leukemia (49). Their analysis further shows that it is the C-terminal IRF ϩ/Ϫ CLL clones as well as three independent NZB IRF4 ϩ/ϩ B1 cells were used for Western blot analysis.…”
Section: Irf4supporting
confidence: 88%
“…Because the DNA binding domain of IRF4 contains a nuclear localization signal, the truncated IRF4 is localized predominantly in the cytosol (49,50). How cytosolic IRF4 suppresses Akt activity remains unclear.…”
Section: Irf4mentioning
confidence: 99%
“…Indeed, multiple studies have recently demonstrated that deletion of IRF4 in mice leads to the development of B-cell leukemia. [12][13][14][26][27][28][29] …”
Section: Mir-125b Overexpression Induces B-cell Cancer Harboring Irf4mentioning
confidence: 99%
“…More recently studies have indicated that IRF4, when overexpressed, functions as an oncoprotein [27]. On the contrary, IRF4 was found down-regulated in some myeloid and early B-lymphoid malignancies [28], and so IRF4 may have different functions in the context of different cell types [29]. IRF4 deficiency facilitates the progression of BCR/ABL-induced B-ALL, while forced expression of IRF4 potently supresses the pathogenesis of BCR/ABL-induced B-ALL [28].…”
Section: Introductionmentioning
confidence: 99%